Mario Lavista Mirrors of Sounds - Alonso- Minutti, Ana R. (Currents in Latin American and Iberian Music, 2023)
Composer, pianist, editor, writer, and pedagogue Mario Lavista (1943-2021) was a central figure of the cultural and artistic scene in Mexico and one of the leading Ibero-American composers of his generation. His music is often described as evocative and poetic, noted for his meticulous attention to timbre and motivic permutation, and his creative trajectory was characterized by its intersections with the other arts, particularly poetry and painting. Lavista was a relational composer; he did not write music as a private enterprise but for and alongside people with whom he established close relations. Understanding analysis as an affective practice, author Ana R. Alonso-Minutti explores the intertextual connections between the multiple texts--musical or otherwise--that are present in Lavista's music. Alonso-Minutti argues that, through adopting an interdisciplinary and transhistorical approach to music composition, Lavista forged a cosmopolitan imaginary that challenged stereotypes of what Mexican music should sound like. This imaginary becomes a strategy of resistance against imperialist agendas placed upon postcolonial peripheries. Departing from traditional biographical and chronological frameworks that exalt masters and masterworks, the author offers a nuanced, personal narrative informed by conversations with composers, performers, artists, choreographers, poets, writers, and filmmakers. Through an innovative mosaic of methodologies, from archival work, to musical and intertextual analysis, oral history, and (auto)ethnography, this book is the first in-depth study of Lavista's compositional career and offers a contextual panorama of the contemporary music scene in Mexico